Effect of temperature and pH on the conversion between free and hidden zearalenone in zein. (30th October 2021) - Tan, Hongxia; Zhou, Hongyuan; Guo, Ting; Zhang, Yuhao; Li, Jiaxin; Zhang, Chi; Ma, Liang
Highlights: Hidden ZEN and free ZEN could transform into each other during food processing. Zein-bound ZEN can be conversed to free ZEN by heat or alkaline treatment. Free ZEN can be changed to zein-bound ZEN under the acid condition. The binding of ZEN with zein enhanced the thermal stability of ZEN. Abstract: Food processing might induce the transformation of hidden ZEN (zein-bound ZEN) in maize. The objective of this study was to assess the effect of processing factors on free ZEN and hidden ZEN. After zein was treated under different temperature and pH, ZEN was quantified in samples before and after in vitro digestion. The ratios of hidden to total ZEN in zein are decreased from 54.25% to 40.74% after thermal treatment and from 54.25% to 0 after alkaline treatment, respectively. Conversely, acid treatment increased the ratio of hidden to total ZEN from 54.25% to 100%. Thus, it can be concluded that thermal or alkaline condition induced the conversion of hidden ZEN to free ZEN while acid condition promoted the ZEN-zein interactions to form the hidden ZEN. Overall, temperature and pH values played a vital role in the conversion of hidden ZEN during food processing.